The effects of competition and corporate political responsiveness on multinational bargaining power - Kim, Woongki (Strategic Management Journal, 1988)
Abstract This paper empirically investigates the effects of competition and corporate political responsiveness on multinational bargaining power. The results indicate that the more intense the competition, the weaker the bargaining power of multinationals vis‐à‐vis that of host governments. Further, higher corporate political responsiveness plays an increasingly important role in safeguarding the bargaining power position of multinationals as competition intensifies. Implications and future research development are suggested.